2013
DOI: 10.1111/tbj.12128
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Micropapillary Carcinoma of the Breast: A Clinicopathologic Study of 103 Cases of an Unusual and Highly Aggressive Variant of Breast Carcinoma

Abstract: Invasive micropapillary carcinoma (IMPC) of the breast is an uncommon, highly aggressive breast cancer that may occur in pure and mixed forms. Our aim in this study is to investigate the relationship between clinical, histopathologic, and immunohistochemical features of pure and mixed IMPC cases diagnosed and treated at our institution. One hundred and three IMPC cases diagnosed at our institution over a period of 19 years have been selected. Clinical, histopathologic features, as well as hormone status and c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
50
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 26 publications
16
50
2
2
Order By: Relevance
“…7,[14][15][16][17]23,24,[37][38][39][40][41][42][43] One study of 624 patients with IMPC revealed a poor prognosis in the patients who had a tumor lacking in estrogen receptor expression. 7 The status of the HER2/neu protein expression or gene amplification in IMPC is not consistent in literature.…”
Section: Immunophenotypementioning
confidence: 99%
See 1 more Smart Citation
“…7,[14][15][16][17]23,24,[37][38][39][40][41][42][43] One study of 624 patients with IMPC revealed a poor prognosis in the patients who had a tumor lacking in estrogen receptor expression. 7 The status of the HER2/neu protein expression or gene amplification in IMPC is not consistent in literature.…”
Section: Immunophenotypementioning
confidence: 99%
“…Some studies showed HER2/ neu þ rates between approximately 10% and 30%, [14][15][16]23,24 whereas others reported between approximately 50% and 80%. 34,38,41,44 Regarding the molecular classification, more cases of IMPC fall into the luminal A and luminal B subtypes than they do with IDC-NOS. 39 The features of IMPC are summarized in the Table. In addition, IMPC should be differentiated from IDC-NOS by retraction artifacts.…”
Section: Immunophenotypementioning
confidence: 99%
“…This carcinoma has been reported to exhibit lymphovascular invasion, lymph node metastasis, local recurrence and distant metastasis at relatively high frequencies, thus exhibiting a more aggressive behavior than invasive ductal carcinoma (IDC) [2], [3]. The rate of incidence of IMPC of the breast has been reported to range from 1.0–8.4% [4], [5], [6], [7], [8], [9], [10]. Due to the low incidence of this breast cancer variant, most studies examining IMPC have small sample sizes; the clinico-pathological characteristics and the clinical prognostic factors of invasive micropapillary carcinoma are therefore not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies compared their cohort of IMPC patients to invasive ductal carcinoma (IDC) controls matched by disease stage and revealed a significantly higher incidence of lymph node metastasis in IMPC patients, particularly for early stage breast cancer [9][10][11][12]14,[23][24][25]28,31,32]. Yu [19-21] b Case series 68 68 NA Tressera et al [26] Case series 15 15 NA Middleton et al [22] Case series 14 14 NA Walsh and Bleiweiss [29] Case series 80 80 "Pure" (n =17), "partial" (n =63, range 5-95%) Wei et al [30] Case series 100 100 475% (n= 42), 50-75% (n=20), 25-50% (n =15), o25% (n=23) Varga et al [27] Case series 11 11 NA Li et al [18] Case series 40 40 "Pure" (n =9), "mixed" (n =31) Chen et al [14] Case series 100 100 NA Shi et al [25] Case series 188 188 "Pure" (n =27), "mixed" (n= 161) Kim et al [11] Cohort 250 38 450% (n= 17), o50% (n =21) Nassar et al [12] Cohort 1400 83 480% (n= 10), "minor proportion" (n =73) Kuroda et al [17] Cohort 671 27 "Some" De La Cruz et al [15] Cohort 1056 16 "Pure" (n =10), "mixed" (n= 6) Zekioglu et al [32] Cohort 2022 53 475% (n= 47), o75% (n =6) Pettinato et al [13] Cohort 1635 62 50-100% (n =40), 25-50% (n =12), o25% (n=10) Yu et al [31] Cohort 2753 72 470% (n= 72) Vingiani et al [28] Cohort 13,278 49 "Pure" (n =49) Paterakos et al [23] Cohort 1287 21 "Pure" (n =21) Gocke et al [10] Cohort 2718 103 "Pure" (n =20), "mixed" (n= 83) Ren et al [24] Cohort 5625 86 NA Chen et al [8,9] however no difference was seen on overall survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these reports are available in the English literature [5][6][7]. The IMPC case series currently available have included a total of 15 male patients [8][9][10][11][12][13] accounting for only 0.005% of invasive breast cancer cases. We present a case of this rare type of breast cancer diagnosed in a male patient and review the current literature to date.…”
Section: Introductionmentioning
confidence: 99%